Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Perilaku Pengelolaan Keuangan UMKM Kuliner dan Locus of control Sebagai Variabel Mediasi di Kecamatan Pasar Kota Jambi - Arief Prasetyo; Tona Aurora Lubis; Agus Solikhin (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of Financial Literacy and Financial Attitudes on Financial Management Behavior mediated by Locus of control in Culinary MSMEs in Pasar District, Jambi City. The analysis tool used is PLS analysis. The results showed that Financial Literacy has a positive and significant effect on Financial Management Behavior, Financial Attitude has no significant effect on Financial Management Behavior, Locus of Control has a positive and significant effect on Financial Management Behavior, Financial Literacy has no significant effect on Locus of Control, Financial Attitude has a significant effect and positive on Locus of Control and Financial Literacy has no significant effect on Financial Management Behavior with Locus of Control as a mediating variable.